Stope boundary optimisation in underground mining based on a heuristic approachStope boundary optimisation in underground mining based on a heuristic approach - Sandanayake, Don Suneth Sameera (Curtin University, 2014)
Stope optimisation is pivotal to maximisation of NPV of an underground mining project. However, none of the algorithms developed for stope optimisation guarantees optimal stope layout due to the computational complexity of the problem. The research proposes an innovative heuristic based algorithm to generate optimal stope layout for a given resource model. The developed algorithm is implemented on a real-case block model representing a Copper deposit and compared with two existing algorithms in case studies.